Measuring the Effectiveness of Anti-Cartel Interventions: A Conceptual Framework - Yannis Katsoulacos; Evgenia Motchenkova; David Ulph (Tinbergen Institute, 2016)
This paper develops a model of the birth and death of cartels in the presence of enforcement activities by a Competition Authority (CA). We distinguish three sets of interventions: (a) detecting, prosecuting and penalizing cartels; (b) actions that aim to stop cartel activity in the short-term, immediately following successful prosecution; (c) actions that aim to prevent the re-emergence of prosecuted cartels in the longer term. The last two intervention activities have not been analyzed in the existing literature. In addition we take account of the structure and toughness of penalties. In this framework the enforcement activity of a CA causes industries in which cartels form to oscillate between periods of competitive pricing and periods of cartel pricing. We determine the impact of CA activity on deterred, impeded, and suffered harm. We derive measures of both the total and the marginal effects on welfare resulting from competition authority interventions and show how these break down into measures of the Direct Effect of interventions (i.e. the effect due to cartel activity being impeded) and two Indirect/Behavioral Effects – on Deterrence and Pricing. Finally, we calibrate the model and estimate the fraction of the harm that CAs remove as well as the magnitude of total and marginal welfare effects of anti-cartel interventions.
Keywords: L4; K21; D43; C73; 330; Antitrust Enforcement; Antitrust Law; Cartel; Oligopoly; Repeated Games